RETRACTED ARTICLE: The lncRNA RHPN1-AS1 downregulation promotes gefitinib resistance by targeting miR-299-3p/TNFSF12 pathway in NSCLC. Issue 14 (18th July 2018) - Li, Xuehao; Zhang, Xin; Yang, Chunlu; Cui, Su; Shen, Qiming; Xu, Shun
Statement of Retraction: We, the Editors and Publisher of the journal Cell Cycle, have retracted the following article: Xuehao Li, Xin Zhang, Chunlu Yang, Sui Cui, Qiming Shen and Shun Xu. The lncRNA RHPN1-AS1 downregulation promotes gefitinib resistance by targeting miR-299-3p/TNFSF12 pathway in NSCLC. Cell Cycle. 2018;17(14):1772-1783. doi: 10.1080/15384101.2018.1496745 Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to address the concerns raised and have not been able to provide their original data. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. The authors do not agree with the retraction. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.